2022
DOI: 10.3390/su141811677
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain-Enabled Open Quality System for Smart Manufacturing: Applications and Challenges

Abstract: In this technological development era, new trends and approaches related to quality management are emerging. Although many studies have focused on quality management in Industry 4.0, new technologies face difficulties in resolving problems arising from lack of trust, transparency, integrity, track-and-traceability, connectivity, and responsibility in evaluating quality. In this article, we discuss the potential of blockchain to deliver business value with transparent quality by introducing a new quality concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Blockchain enables SC to provide capabilities to the firm to handle expected and unexpected demand/supply changes with accurate forecasting using real-time information, end-to-end visibility and transparency in the SC function, which leads to an increase in firm performance (Kayikci et al, 2022;Kumar et al, 2020). With the adoption of blockchain for SC, the firm can obtain several benefits such as 1) an effective knowledge-sharing platform among SC members (internal and external), 2) strengthening the firm's risk management, 3) accurate decision-making, 4) SC flexibility, 5) enhancing resilience, which highly indicates that the firm increases its SC robustness capabilities (Ali et al, 2022;Dasaklis et al, 2022;Dutta et al, 2020;Ghode et al, 2020). Furthermore, the blockchain provides strong integration between internal and external SC members and increases SC agility by providing an information-sharing platform and superior cybersecurity for financial transactions (Haroon et al, 2019;Muheidat et al, 2022).…”
Section: Hypotheses Development and Conceptual Frameworkmentioning
confidence: 99%
“…Blockchain enables SC to provide capabilities to the firm to handle expected and unexpected demand/supply changes with accurate forecasting using real-time information, end-to-end visibility and transparency in the SC function, which leads to an increase in firm performance (Kayikci et al, 2022;Kumar et al, 2020). With the adoption of blockchain for SC, the firm can obtain several benefits such as 1) an effective knowledge-sharing platform among SC members (internal and external), 2) strengthening the firm's risk management, 3) accurate decision-making, 4) SC flexibility, 5) enhancing resilience, which highly indicates that the firm increases its SC robustness capabilities (Ali et al, 2022;Dasaklis et al, 2022;Dutta et al, 2020;Ghode et al, 2020). Furthermore, the blockchain provides strong integration between internal and external SC members and increases SC agility by providing an information-sharing platform and superior cybersecurity for financial transactions (Haroon et al, 2019;Muheidat et al, 2022).…”
Section: Hypotheses Development and Conceptual Frameworkmentioning
confidence: 99%
“…In this study, 12 SC practices were derived from identified SC types, and their needs for blockchain were discussed according to the essential blockchain features of each type. An SC network can be classified as agile (responsiveness) or lean (eliminating waste) according to the operational needs of the SC [16,[36][37][38][39]. Furthermore, SCM-related firm performance is generally based on five dimensions: increases in sales, more accurate costing, increases in coordination with vendors, increases in coordination between departments, and increases in coordination with customers [15,16].…”
Section: Agile and Lean Supply Chain Supply Chain Management-related ...mentioning
confidence: 99%
“…Numerous scholars have produced a large amount of research on applying these two technologies in quality traceability. Shujaat A. et al [4] reviewed the application scenarios of the blockchain in the field of intelligent manufacturing. They proposed constructing an open quality system to expand the transparency of industrial product quality.…”
Section: Introductionmentioning
confidence: 99%